2010
DOI: 10.1002/pon.1865
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐level factors in colorectal cancer screening: a review of the literature on the relation of individual‐level health behavior constructs and screening behavior

Abstract: Compliance with colorectal cancer screening recommendations requires considerable conscious effort on the part of the individual patient, making an individual's decisions about engagement in screening an important contributor to compliance or noncompliance. The objective of this paper was to examine the effectiveness of individual-level behavior theories and their associated constructs in accounting for engagement in colorectal cancer screening behavior. We reviewed the literature examining constructs from for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 41 publications
10
101
4
3
Order By: Relevance
“…Consistent with many studies which found that recommendations from healthcare professionals were related to higher screening participation (Beydoun and Beydoun, 2008;Kiviniemi et al, 2011), we also found that cues to actions was a facilitator of CRC screening. Providing health information is expected to alleviate people's perceived negative effects of CRC on their mental status and current personal and family lives as well as to reduce their knowledge barriers in terms of health consequences and accessibility to CRC screening.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with many studies which found that recommendations from healthcare professionals were related to higher screening participation (Beydoun and Beydoun, 2008;Kiviniemi et al, 2011), we also found that cues to actions was a facilitator of CRC screening. Providing health information is expected to alleviate people's perceived negative effects of CRC on their mental status and current personal and family lives as well as to reduce their knowledge barriers in terms of health consequences and accessibility to CRC screening.…”
Section: Discussionsupporting
confidence: 90%
“…As is clearly indicated by the findings, access difficulties of screening may be an important barrier to screening among Chinese older people although the sample had a moderate level of knowledge. Such a finer classification of barriers may provide an explanation for the inconsistent findings in the literature that 80 (73.3%) out of 109 found predicted direction, 28 (25.7%) found no relation and one found opposite direction for barriers with CRC screening in a previous review (Kiviniemi et al, 2011). Nevertheless, our findings suggest that special health programmes targeting Chinese older people to promote CRC screening should include a component on increasing knowledge regarding access, financial resources, time and environmental factors relating to the screening service and the screening procedures.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…the belief that screening is effective), which is a key construct in the Health Belief Model, which has been found useful in trying to predict CRC screening uptake. 229 Third, we reduced perceived barriers to screening by affirming that 'it is never too late to screen' and increased self-efficacy by offering guidance about how to seek further guidance.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…These include the person's knowledge and beliefs about the intervention, self-efficacy, individual stage of change, individual identification with the organization, among other personal attributes (Damschroder et al, 2009). More recently, and relevant to the discussion of provider adoption of EBPs, The Integrated Model (Ajzen, 1991;Grant & Wrzesniewski, 2010;Henshaw & Freedman-Doan, 2009;Kiviniemi, Bennett, Zaiter, & Marshall, 2011) has been advanced to illuminate why some people engage in particular behaviors while others do not. The Integrated Model identifies intention to perform a behavior as a direct determinant of behavior change.…”
Section: Individual Providersmentioning
confidence: 99%